Free convection boundary layer flow on a solid sphere in a nanofluid with viscous dissipation - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Ishak (UTM Press, 2019)
Present study considers the mathematical model of free convection boundary layer flow and heat transfer in a nanofluid over a solid sphere with viscous dissipation effect. The transformed partial differential equations are solved numerically using the Keller-box method. The numerical values for the reduced Nusselt number, reduced Sherwood number and the reduced local skin friction coefficient are obtained, as well as concentration profiles, temperature profiles and velocity profiles are illustrated graphically. Effects of the pertinent parameters, which are the Prandtl number, buoyancy ratio parameter, Brownian motion parameter, thermophoresis parameter, Lewis number and Eckert number are analyzed and discussed. It is found that the increase of Brownian motion parameter promoted the reduce of concentration boundary layer thickness while thermophoresis parameter did oppositely. It is worth mentioning that the results reported here are important for the researchers working in this area which can be used as a reference and comparison purposes in the future.